Pemberdayaan Usaha Karawo Desa Mongolato Kecamatan Telaga Kabupaten Gorontalo Selama Masa Pendemi Covid-19 - Aminudin Aminudin; Nur Hasanah A. Husain; Riskayanti Batalipu (Wisanggeni : Jurnal Pengabdian Masyarakat, 2021)
This research uses an Asset-Based Community Development approach. This Study aims to empower the potential of the community so that they have the power to recognize and utilize all the strengths and assets they have for the good off the community. The asset referred too here is Karawo as a product of the typcal cultural arts of the province of Gorontalo Indonesian. Karawo is a technique for forming ornaments on textiles, through a process of designing, slicing, and removing certain parts of the textile fiber to make the base plane, and re-stitching the pulled textile fibers to form motifs. Karawo business in Mongolato Village, Kec. Telaga, Kab. Gorontalo started from 2004 until now and has gone global. The Covid-19 epidemic has emerged and is of particular concern to economists and business people. This is because it is estimated that the global economy will slow down following a stipulation from the WHO which mentions the corona outbreak as a pandemic affecting the business world. during the Covid-19 pandemic, the Karawo business was still ongoing or ongoing. The Covid-19 pandemic did not have a negative impact on the typical Gorontalo karawo business actors, precisely in Mongolato Village, Kec. Telaga, Kab. Gorontalo. In fact, Karawo's business income has increased due to the Covid-19 pandemic.